Improving Concept Understanding and Learning Outcomes of Elementary School Students through Science Textbooks Based on Learning Cycle 7E Model - Rena Elia; Solfema Solfema; Yalvema Miaz; Zelhendri Zen (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to develop textbooks based on the Learning Cycle 7E approach for learning Science of Nature and Environment (IPAS) in grade IV Elementary School. The textbook development process includes needs analysis, design, validation, revision, and implementation. The validity of the coursebook was evaluated by experts in the aspects of material, media, and language. Practicality was assessed by teachers and students, while the effectiveness was tested using paired t-test. The results showed that the developed coursebooks were highly valid in terms of material, media, and language, based on expert validation. Teachers and students rated the textbook as very practical to use. The effectiveness test indicated a significant increase in students' understanding and learning outcomes after using the textbook. In conclusion, this Learning Cycle 7E-based textbook is effective and relevant in improving the quality of IPAS learning in grade IV SD.